PENGARUH PENGEMBANGAN KEPROFESIAN, KECERDASAN EMOSIONAL, DAN BEBAN KERJA TERHADAP KUALITAS KERJA DI SMK NEGERI KELOMPOK PARIWISATA SENI DAN KERAJINAN KOTA YOGYAKARTA TAHUN AJARAN 2012/2013 (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
This study aimed to determine the influence of proffesion development, emotional intellegence and on quality of work in Vocational High School of Tourism, Arts and Craft Group of Yogyakarta City in the Academic Year of 2012/2013. The study population numbered 341 people. The sampling method used a quota proportional random sampling numbering 174 people. The data analysis technique used were desciptive and analysis multiple regression and partial correlation.The results indicate that the proffesion development, emotional intellegence and workload has a positive and significant influence on the quality of teacher‟s work. The effective controbution given by the proffession development variable toward the quality teacher‟s work is 11,12 %, the effective contribution given by the emotional intellegence variable toward the quality of teacher‟s work is 18,70 % and the effective contribution given by the workload variable toward the quality of teacher‟s work is 10,56 % so that the total of effective contribution is 40,40 %. It is means that the other influeces are 59,60 %, beside the proffesion development, emotional intellegence that affect the quality of work.